Long-term prognosis of patellar tendinopathy (jumper`s knee) in young, elite volleyball players: tendon changes 11 years after baseline - Visnes, H.; Bache-Mathiesen, L. K.; Yamaguchi, T.; Gilhuus, H. P.; Algaard, K. R. H.; Hisdal, E.; Bahr, R. (The American Journal of Sports Medicine, 2024)
Background: The long-term prognosis of jumper's knee and whether structural changes in the patellar tendon persist is unknown.